2020
DOI: 10.1016/j.ijhcs.2020.102499
|View full text |Cite
|
Sign up to set email alerts
|

Personal informatics and negative emotions during commuter driving: Effects of data visualization on cardiovascular reactivity & mood

Abstract: Mobile technology and wearable sensors can provide objective measures of psychological stress in everyday life.Data from sensors can be visualized and viewed by the user to increase self-awareness and promote adaptive coping strategies. A capacity to effectively self-regulate negative emotion can mitigate the biological process of inflammation, which has implications for long-term health. Two studies were undertaken utilizing a mobile lifelogging platform to collect cardiovascular data over a week of real-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Marsden and Pingry (2018) reported that interviews, field‐experiments, quasi‐experiments, controlled laboratory experiments, empirically observed and third party fee‐for‐service data are alternative ways to gather numerical data in IS research. Moreover, with the recent advances in technology, wearable sensors, electromyographic signals and eye movement data can be used to infer human behavioural intentions (Fairclough & Dobbins, 2020; Park et al, 2016). As such, these tools could be used a complement to conventional research methods.…”
Section: Discussion and Future Research Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…Marsden and Pingry (2018) reported that interviews, field‐experiments, quasi‐experiments, controlled laboratory experiments, empirically observed and third party fee‐for‐service data are alternative ways to gather numerical data in IS research. Moreover, with the recent advances in technology, wearable sensors, electromyographic signals and eye movement data can be used to infer human behavioural intentions (Fairclough & Dobbins, 2020; Park et al, 2016). As such, these tools could be used a complement to conventional research methods.…”
Section: Discussion and Future Research Agendamentioning
confidence: 99%
“…This is one area that might need consideration while designing data collection tools for flow-based studies. Marsden and Pingry (2018) (Fairclough & Dobbins, 2020;Park et al, 2016). As such, these tools could be used a complement to conventional research methods.…”
Section: Proposition 1c Flow Experience Will Have Independent As Wellmentioning
confidence: 99%
“…Users can view the data from sensors and objectively measure the psychological pressure in daily life to improve self-awareness and promote emotion regulation or behavior change. A notable experiment showed that interactive data visualization could reduce the user’s heart rate during traffic congestion ( Fairclough and Dobbins, 2020 ). With the proposal of the meta-universe, virtual reality has attracted more attention.…”
Section: Introductionmentioning
confidence: 99%
“…These can monitor various parameters of the observed students (and teachers) during the process of teaching and learning in a complex physical and sociological environment such as a classroom. Autonomous wearable measurement devices that are worn on the user’s body to monitor the user’s physical, (psycho)physiological, mental, emotional, and behavioral activity are currently being used with increasing regularity [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] but are not widely used in empirical research in educational science. They are usually used to measure students’ physical activity, and few are used to measure students’ psychophysiology [ 35 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%